TECHNOLOGICAL DEVELOPMENT AND THE TRANSFORMATION OF HUMAN CONSCIOUSNESS - Khonzoda Komilova Muzaffar kizi, Mukhimjon Akhunov Mukhammadaminovich (International Multidisciplinary Journal for Research & Development, 2025)
This article explores the profound influence of technological development on the evolution of human consciousness. It investigates how the digital environment, artificial intelligence, and information flows reshape human perception, communication, and intellectual processes. The author emphasizes both the constructive and limiting aspects of technology, revealing its ability to expand human cognition while simultaneously creating dependency on algorithmic systems. Particular attention is paid to the philosophical and psychological implications of living in a technologically mediated world. The study concludes that true progress requires cultivating a conscious and self-regulating mind capable of controlling — rather than being controlled by — technology.